A randomized controlled trial comparing the efficacy, tolerability, and cost of oral iron preparations in iron‐deficiency anemia in pregnancy. Issue 11 (6th September 2021) - Gamad, Nanda; Saha, Pradip Kumar; Sharma, Prashant; Suri, Vanita; Chakrabarti, Amitava; Saha, Lekha
Abstract: Objective: To evaluate the efficacy, tolerability, and cost of four commonly prescribed oral iron preparations: ferrous sulfate (FS), ferrous fumarate (FF), ferrous ascorbate (FA), and carbonyl iron (CI) in the treatment of iron‐deficiency anemia (IDA) in pregnant women. Methods: It was a prospective, randomized, open‐label, blinded endpoint (PROBE) design with four parallel active control groups: FS, FF, FA, CI. The primary outcome was the proportion of participants becoming non‐anemic (Hb ≥ 11 g%) at the end of the study period. The secondary outcomes were the proportion of participants achieving normal red blood corpuscular indices such as mean corpuscular volume, mean corpuscular hemoglobin, and mean corpuscular hemoglobin concentration; the proportion of participants achieving normal iron indices such as serum iron, serum ferritin, total iron‐binding capacity, and transferrin saturation; and comparison of incidence of any adverse events between treatment groups and comparison of costs of individual drug therapy between treatment groups. Results: One hundred and twenty patients were randomized to four different groups ( n = 30). The results of the present study show that all the four iron salts at the dose of 200 mg elemental iron per day were equally effective in improving hemoglobin concentration and other hematological parameters. The adverse effects were more common in the FF group (56.7%). The pharmacoeconomic analysis showed that all the drugs are equally cost‐effective. Conclusion: To conclude from the results of the present study, it can be said that FS, FF, FA, and CI are equally effective in treating IDA and they can be prescribed interchangeably.